Enablers & barriers to online and e-learning for health professionals in Pakistan: a formative research - Ladhani, Zahra Saleem; Amira Mushtaq Khan; Zulfiqar Ahmed Bhutta (Journal of the Pakistan Medical Association, 2025)
Objective: To design a continuous professional development programme pertaining to integrated nutrition, health, and Water Sanitation and Hygiene interventions for health professionals. Method: The scoping review was conducted under the aegis of a capacity-building project led by the Centre for Global Child Health, Canada, and comprised systematic search for scholarly publications and grey literature published between January 2013 and September 2023, using Best Evidence Medical Education guide on Google Scholar and PubMed data bases as well as manual search in journals focussing on health professionals education. Data on enablers and barriers to e-learning in the specific context of health professions was compiled and synthesised. This was followed by in-depth interviews of policy-makers, educators and health professionals working in the field of nutrition. Results: Of the 1,768 publications identified, 41(2.3%) were analysed in detail. Of the 15 key informants interviewed, 7(46.6%) were HPs, while 4(26.7%) each were police-makers and facilitators or designers of online modules. Under the two broad categories of “enablers” and “barriers”, five subthemes emerged for each. The subthemes related to enablers included personal, content and design, quality of facilitators, peer connectivity, and social networking. The subthemes related to barriers were structural, cultural, curricular and content, human resources, and financial. Conclusion: In Pakistan, the corona virus disease-2019 pandemic brought about a forced digital transformation for health professions students. Blended learning emerged as an effective e-learning model. To inform the development, implementation and sustainability of online continuous professional development of health professionals, a guiding framework comprising various elements, like financing mechanism, appropriate materials and activities, communication strategy, and an evaluation process, incorporating regulatory perspective, contextual factors and clear objectives is essential. Key Words: Online education, E-learning, Barriers, Enablers, Health professionals, Continuous professional development.